Investigations on drop penetration and wetting characteristics of powder-liquid systems in relation to the mixing of acrylic bone cement. (20th October 2010) - McEleney, Patrick; Walker, Gavin; Orr, John; Dunne, Nicholas J.
This study investigated methyl methacrylate – polymethyl methacrylate powder bed interactions through droplet analyses, using model fluids and commercially available bone cement. The effects of storage temperature of liquid monomer and powder packing configuration on drop penetration time were investigated. Methyl methacrylate showed much more rapid imbibition than caprolactone due to decrease in both contact angle and fluid viscosity. Drop penetration of caprolactone through polymethyl methacrylate increased with decrease in bed macro-voids and increase in bulk density as predicted by the modified constant drawing area penetration model and confirmed by drop penetration images. Linear relationships were found between droplet mass and drawing area with imbibition time. Further experiments showed gravimetric analysis of the polymerised methyl methacrylate – polymethyl methacrylate matrix under various storage temperatures correlated with Reynolds number and Washburn analyses. These observations have direct implications for the design of mixing and delivery systems for acrylic bone cements used in orthopaedic surgery.